Development of an O-ring from NR/EPDM filled silica/CB hybrid filler for use in a solid oxide fuel cell testing system. (August 2020) - Chea, Sophos; Luengchavanon, Montri; Anancharoenwong, Ekasit; Techato, Kua-anan; Jutidamrongphan, Warangkana; Chaiprapat, Sumate; Niyomwas, Sutham; Marthosa, Sutida
Abstract: This research presents the effects of oxygen pressure and ambient temperatures on the crack behavior of O-rings from a semi-EV of NR/EPDM rubber with silica/CB filler, exposed to the inlet flow and outflow oxygen pressure in a Solid Oxide Fuel Cell (SOFC) environment. Blends of NR/EPDM were prepared with various ratios of silica/CB filler at 00/60, 10/50, 20/40, 30/30, 40/20, 50/10, and 60/00 phr. The fabricated O-ring complied with the standard for O-rings (TIS 2728-2559), with a minimum hardness of 65–75 Shore A, minimum tensile strength of 9 MPa, minimum elongation at break of 200%, and a minimum 100% modulus of 2.7 MPa. The mechanical properties of the compounds were tested, and the appropriate compound was chosen to make the O-rings to test in SOFC. The crack morphology of the fabricated O-rings was investigated and compared with a commercial O-ring after testing in the SOFC. As a result, the compound with silica/CB of 40:20 ratio provided the optimum mechanical properties, and passed the criteria standard of TIS 2728-2559. The mechanical properties of the prepared and commercial O-rings were similar ( P -value of commercial with 60/00 = 0.273, 50/10 = 0.273, 40/20 = 0.144, 30/30 = 0.465, 20/40 = 0.465, 10/50 = 1.000 and 00/60 = 0.273; all > 0.05) and and both could still be continued to be used in SOFC despite some inner cracks after 24 h. The price of the prepared O-ring is cheaper than the commercial O-rings due to the low price of NR used in its formulation. Therefore, a prepared O-ring can be used in a SOFC, or other applications due to their mechanical properties and their reasonable price. Highlights: Blends of natural and ethylene-propylene-diene-monomer rubbers were prepared with silica and carbon black hybrid fillers. All formulations were prepared in the internal mixture and on a two-roll mill machine. O-rings were moulded from semi-efficient sulphur vulcanization. Mechanical properties of all compounds before and after ageing were tested. O-rings were exposed to oxygen gas pressure at flow rate of 0.5 L/min and ambient temperature in solid oxide fuel cell (SOFC).